Pemetaan Tingkat Bahaya Erosi dengan Pemanfaatan Teknologi Drone di DTA Cipaheut Sub DAS Cikapundung Hulu - Elita Cahyani; Abraham Suriadikusumah; Apong Sandrawati (Media Agribisnis, 2023)
Technology in the field of mapping is constantly evolving to provide convenience for human work. One of the innovations that are developing in today’s modern era is drone or Unmanned Aerial Vehicle (UAV). Erosion mapping and erosion measurements are carried out to determine the potential risk of erosion in certain areas. The erosion risk map shows the distribution of erosion hazard levels in an area. The objective of this research is to determine erosion prediction and erosion hazard levels spatially based on USLE (Universal Soil Loss Equation) method using drone. The used of UAV for collecting data to generate soil erosion risk map at detail scale based on USLE method is relatively infrequently done in Indonesia. The research was conducted in Cipaheut Watershed, Cikapundung Hulu Sub-watershed, Cimenyan, Cimenyan, Bandung Regency, West Java. The results of the study show that the role of drone is very helpful in mapping general conditions and land use spatially. In addition, drones are able to provide actual data sources to identify the physical factors needed in the USLE method of erosion calculations such as LS, C and P factors. Erosion prediction and erosion hazard levels can be calculated using data acquired from drones. There are 8 SPLs with a total land area of ​​225.10 Ha. SPL 5 with the use of dry land and steep slope have the highest erosion prediction values ​​of 703.1207 tons/ha/year and an erosion hazard index of 87.8901 tons/ha/year with a very high level of erosion hazard.